Analisis Faktor-Faktor yang Berhubungan dengan Cakupan Imunisasi Dasar Lengkap pada Bayi di Wilayah Kerja Puskesmas Ladang Tuha Aceh Selatan - Dhiaul Asyura; Agustina Agustina; Dedi Andria (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Basic immunization completeness is an effective measure to prevent potentially fatal diseases in infants. However, the coverage of complete basic immunization in Aceh in 2022 remained low at 38.4%, far below the government target of 84.2%. This study aimed to analyze factors associated with the completeness of basic immunization among infants in the working area of Ladang Tuha Health Center, South Aceh. This study employed a descriptive analytical design with a cross-sectional approach. The study population consisted of all mothers with infants aged 12–24 months, totaling 107 individuals. A sample of 36 respondents was selected using random sampling. Data were collected through questionnaires and interviews from May 22 to May 29, 2025. Data analysis was performed using the Chi-square test with a 95% significance level. The univariate analysis showed that 41.7% of infants had received complete basic immunization, while 58.3% had not. Most mothers had poor knowledge (55.6%), close access to health services (97.2%), low family support (58.3%), and less supportive social environments (69.4%). Bivariate analysis revealed significant associations between immunization completeness and maternal knowledge, family support, and social environment. However, access to health services was not significantly associated with basic immunization completeness. Routine health education, family involvement, and strengthening immunization programs are needed to improve basic immunization coverage.